The Improvement of Fishbowl Technique on Tenth Grade Speaking Achievement - Khair, Ummul; Telaumbanua, Faozatulo; Simorangkir, Eflin Novalynda; Fatimah; Lestari, Cicik Sri (CV. Doki Course and Training, 2023)
This research is concerned with the influence of the fishbowl on the speaking achievement of the tenth-grade students of SMAN 1 GAS INHIL RIAU. The objectives of this study were to find out: a) whether or not there was a significant influence on speaking achievement of the tenth-grade students of SMAN 1 GAS INGIL RIAU who were taught by using the fishbowl technique and those who were not, and b) whether or not there was a significant difference of speaking achievement between the tenth-grade students of SMAN 1 GAS INHIL RIAU who were taught by using fishbowl technique. The population was the tenth-grade students of SMAN 1 GAS INHIL RIAU in the academic year 2022/2023. The purposive Sampling technique was used to take a sample of this study which consisted of 80 students. This study used a quasi-experimental design, there were an experimental group and a control group. Both of them were given a pre-test and post-test (before and after treatment). In analysing the data, paired sample t-test and independent sample t-test would be applied. Based on statistical analysis, the result of paired sample t-test showed that t-obtained (14.835) > t-table (2.079) which means that the students’ speaking achievement was significantly influenced. Then the result independent sample t-test, the value of t-obtained (3.592) was higher than the critical value of t-table (2.079). It means that there was a significant difference between SMAN 1 GAS INHIL RIAU who were taught by using a fishbowl and those who were not.